Meningkatkan Kemampuan Mengenal Keaksaraan Awal melalui Permainan Kartu Suku Kata dengan Model Pembelajaran Kooperatif pada Anak Kelompok B TK Dharma Wanita Bansari Temanggung Semester II Tahun 2018/2019 - Romiyati Romiyati (Universitas PGRI Semarang, 2021)
One aspect of language that needs to be prepared and developed for kindergarten age children to face the next level of education is the ability to recognize early literacy. The ability to recognize early literacy is an ability that looks simple, but this ability must be mastered by kindergarten children because the introduction of letters including initial capital has reading skills. To master reading skills in kindergarten, various ways are needed in the learning process in recognizing early literacy, one of which is by using syllable card media so that children are interested in new things so that they are easy to receive information. The aims of this study were: 1) to find out the steps to increase the ability to recognize early literacy through syllable card games with cooperative learning models, 2) to determine the magnitude of the increase in ability to recognize early literacy through syllable card games with cooperative learning models in group children. B TK Dharma Wanita Bansari Temanggung Semester II 2018/2019. The subjects of this study were students of Group B TK Dharma Wanita Bansari totaling 20 children. Data collection methods used are observation, interviews, and documentation. The conclusion of this study is that the ability to recognize early literacy of children in group B of Dharma Wanita Bansari Kindergarten can be improved using syllable card media games with cooperative learning models. In the learning process of the syllable card game, each child holds the syllable card directly and plays it according to the researcher's instructions, namely reading words based on writing, connecting and mentioning simple writing with symbols that symbolize, making scribbles or writing in the form of letters or words. The increase in the ability to recognize early literacy is in the initial condition by 15%, increasing in Cycle I to 30%, and Cycle II increasing to 85%. So, from pre-action to Cycle II, there was an increase of 70%.